WCDMA for UMTS : HSPA evolution and LTE - Holma, Harri, 1970-; Toskala, Antti (Wiley, 2010)
Now in its fifth edition, the bestselling book on UMTS has been updated to cover 3GPP WCDMA and High Speed Packet Access (HSPA) from Release 99 to Release 9. Written by leading experts in the field, the book explains HSPA performance based on simulations and field experience, and illustrates the benefits of HSPA evolution (HSPA+) both from the operators and from the end user€s perspective. It continues to provide updated descriptions of the 3GPP standard including the physical layer, radio protocols on layers 1-3 and a system architecture description. The challenges and solutions regarding t.